Práticas educativas para o ensino de educação ambiental no Colégio Estadual Tiradentes de Umuarama, PR - Oliveira, Janaina Zavilenski de (2014)
This work aims to present a study on how environmental education when applied in schools can contribute to the formation of conscious citizens. Through questionnaires for teachers and elementary school students from the College of Tiradentes Umuarama / PR, we identified what level of participants' knowledge of environmental issues, and pointed up the main difficulties faced by teachers to deal with environmental issues in the classroom in an interdisciplinary way. The survey results showed that environmental education in this school is presented through Project Trees of Life, and in some isolated disciplines. There are many challenges faced by teachers in the teaching of environmental education in the classroom, such as the students' disinterest in the subject and the lack of knowledge on the subject by teachers. The Environmental Education projects in schools aim to promote student awareness of their role and their contribution to the preservation of the environment in which they live.